Potential mechanism of thymosin-α1-membrane interactions leading to pleiotropy: experimental evidence and hypotheses. (31st May 2018) - Mandaliti, Walter; Nepravishta, Ridvan; Pica, Francesca; Vallebona, Paola Sinibaldi; Garaci, Enrico; Paci, Maurizio
ABSTRACT: Introduction : Thymosins have been extracted, characterized, and identified from Thymus. The Thymosins are hormones whose therapeuric applications have seen a recent increase. The action of Thymosin α1 is based on the stimulation of the immune response with a large number of results in a variety of pathologies. The absence of a specific receptor prompted us to investigate the direct interaction with membranes, particularly those exposing phosphatidylserine thus contributing to assess the Thymosin α1's pleiotropy. Areas covered : The interaction with membranes has been studied with a number of models indicating that Thymosin α1 interacts preferentially with negative regions of the membrane (SDS mixed with dodecylphosphocholine) or, better, with vesicles of dipalmitoylphosphatidylcholine with exposed phosphatidylserine. Expert opinion : The study of the role of the membrane in the mechanism of action of Thymosin α1 indicated that probably the first interaction occurs at the membrane level with recognition of negative surface due to the phosphatidylserine exposure. Upon assuming a conformation, with two helices with a disordered tract in between, it diffuses on the membrane surface by lateral diffusion. Then the interaction with membrane receptor(s) causes a membrane complex to be formed, with an activation of a signalling cascade. This can be considered the basis of its pleiotropy. Differences in structuration mechamism of Thymosin β4 was outlined.